2022
DOI: 10.1021/acssynbio.1c00516
|View full text |Cite
|
Sign up to set email alerts
|

CS-Cells: A CRISPR-Cas12 DNA Device to Generate Chromosome-Shredded Cells for Efficient and Safe Molecular Biomanufacturing

Abstract: Synthetic biology holds great promise for translating ideas into products to address the grand challenges facing humanity. Molecular biomanufacturing is an emerging technology that facilitates the production of key products of value, including therapeutics and select chemical compounds. Current biomanufacturing technologies require improvements to overcome limiting factors, including efficient production, cost, and safe release; therefore, developing optimum chassis for biomolecular manufacturing is of great i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The development of transposase component engineering may expand its application in eukaryotic cells in the future. A latest study reported a surprising finding that the designed CRISPR/Cas12 DNA device can degrade the native chromosome and convert bacterial cells into biosynthetic chassis for high-efficiency molecular biomanufacturing [ 80 ]. As a consequence, with the unremitting efforts of researchers from all over the world, the new functions and new types of Cas proteins will be further discovered and deciphered, which will further broaden their diverse biotechnological applications, so as to better utilize the CRISPR/Cas system to serve humans.…”
Section: Discussionmentioning
confidence: 99%
“…The development of transposase component engineering may expand its application in eukaryotic cells in the future. A latest study reported a surprising finding that the designed CRISPR/Cas12 DNA device can degrade the native chromosome and convert bacterial cells into biosynthetic chassis for high-efficiency molecular biomanufacturing [ 80 ]. As a consequence, with the unremitting efforts of researchers from all over the world, the new functions and new types of Cas proteins will be further discovered and deciphered, which will further broaden their diverse biotechnological applications, so as to better utilize the CRISPR/Cas system to serve humans.…”
Section: Discussionmentioning
confidence: 99%